2011
DOI: 10.1371/journal.pone.0024278
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study Examining Adherence to Guidelines in Diabetes Care According to Different Definitions of Adequacy and Timeliness

Abstract: BackgroundPerformance indicators assessing quality of diabetes care often look at single processes, e.g. whether an HbA1c test was conducted. Adequate care, however, consists of consecutive processes which should be taken in time (clinical pathways). We assessed quality of diabetes care by looking at single processes versus clinical pathways. In addition, we evaluated the impact of time period definitions on this quality assessment.MethodologyWe conducted a cohort study in 2007–2008 using the GIANTT (Groningen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 45 publications
1
50
0
Order By: Relevance
“…The time period of 120 days takes into account possible delays until the next regular visit because of competing demands or clinical uncertainty. 32,33 Switches from one drug to another or dosage increases coinciding with dosage decreases within a 7-day time window were not classified as treatment intensification. However, a switch to insulin was always considered intensification.…”
Section: Performance Measures Linked To Glycemic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The time period of 120 days takes into account possible delays until the next regular visit because of competing demands or clinical uncertainty. 32,33 Switches from one drug to another or dosage increases coinciding with dosage decreases within a 7-day time window were not classified as treatment intensification. However, a switch to insulin was always considered intensification.…”
Section: Performance Measures Linked To Glycemic Controlmentioning
confidence: 99%
“…This is the period in which an effect from the treatment can be expected. 33 For patients without glucoselowering treatment or treatment intensification, glycemic control was assessed similarly after a random date drawn from the observed distribution of prescription dates in patients with glucose-lowering treatment or treatment intensification.…”
Section: Glycemic Control Outcomementioning
confidence: 99%
“…Regardless, with proper diagnosis, monitoring, and adaption and adherence to a prescribed lifestyle [44][45][46], type-2 DM can be prevented, or if present, reasonably managed. A key element to the effective and efficient management of type-2 DM is accurate, accessible, costeffective diagnostic tests for monitoring blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that GPs base the treatment changes on a longer period. A previous study showed, however, that an extended period of 180 days does not significantly lead to a higher number of changes after elevated levels (28). Finally, we only had information about changes in drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The definitions of potential overtreatment were based on those suggested by Kerr et al (14) and validated by assessing the association between overtreatment and experiencing an adverse drug event. The definitions of potential undertreatment were derived from practice guidelines (7,14,(26)(27)(28) We used a period of 120 days to assess changes in treatment after the index date to capture clinical actions that were postponed to the next regular visit, which is commonly after 3 months in the Netherlands (28,29). The therapeutic groups of BP-and glucoselowering treatment included seven and eight drug classes, respectively ( Table 1).…”
Section: Outcome Measuresmentioning
confidence: 99%